Organoids as tools for fundamental discovery and translation—a Keystone Symposia report. Issue 1 (30th September 2022) - Cable, Jennifer; Lutolf, Matthias P.; Fu, Jianping; Park, Sunghee Estelle; Apostolou, Athanasia; Chen, Shuibing; Song, Cheng Jack; Spence, Jason R.; Liberali, Prisca; Lancaster, Madeline; Meier, Anna B.; Pek, Nicole Min Qian; et al.
Abstract: Complex three‐dimensional in vitro organ‐like models, or organoids, offer a unique biological tool with distinct advantages over two‐dimensional cell culture systems, which can be too simplistic, and animal models, which can be too complex and may fail to recapitulate human physiology and pathology. Significant progress has been made in driving stem cells to differentiate into different organoid types, though several challenges remain. For example, many organoid models suffer from high heterogeneity, and it can be difficult to fully incorporate the complexity of in vivo tissue and organ development to faithfully reproduce human biology. Successfully addressing such limitations would increase the viability of organoids as models for drug development and preclinical testing. On April 3–6, 2022, experts in organoid development and biology convened at the Keystone Symposium "Organoids as Tools for Fundamental Discovery and Translation" to discuss recent advances and insights from this relatively new model system into human development and disease. Abstract : Complex three‐dimensional in vitro organ‐like models, or organoids, offer a unique biological tool with distinct advantages over two‐dimensional cell culture systems, which can be too simplistic, and animal models, which can be too complex and may fail to recapitulate human physiology and pathology. Significant progress has been made in driving stem cells to differentiate into different organoid types, though several challenges remain.